2002
DOI: 10.1053/rmed.2001.1218
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory marker serum eosinophil cationic protein (ECP) compared with PEF as a tool to decide inhaled corticosteroid dose in asthmatic patients

Abstract: The objective of this study was to compare the inflammatory marker eosinophil cationic protein (ECP) with peak expiratory flow (PEF) in determining the therapeutic needs of inhaled corticosteroids in asthma patients assessed as asthma symptoms. A randomized, single-blind study over 6 months was performed at six specialist centres in Europe. In total, 164 adult patients with moderate to severe symptomatic asthma and regular use of inhaled corticosteroids were included. After a run-in period of 2 weeks patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…Moreover, serum ECP does not appear to predict a response to corticosteroid therapy (341). Finally, a randomized trial comparing a serum ECP-based algorithm for managing asthma with a conventional algorithm found no improvement in symptom scores, in spite of increased doses of ICS (342).…”
Section: Serum Eosinophil Cationic Proteinmentioning
confidence: 99%
“…Moreover, serum ECP does not appear to predict a response to corticosteroid therapy (341). Finally, a randomized trial comparing a serum ECP-based algorithm for managing asthma with a conventional algorithm found no improvement in symptom scores, in spite of increased doses of ICS (342).…”
Section: Serum Eosinophil Cationic Proteinmentioning
confidence: 99%
“…Кроме того, сывороточная концентрация ЭКП не прогнозирует ответа на кортикостероидную те рапию [341]. Наконец, в рандомизированном иссле довании, сравнивавшем традиционный алгоритм ведения больных с астмой с алгоритмом, ориентиро ванным на сывороточную концентрацию ЭКП, не выявлено уменьшения выраженности симптомов, несмотря на повышение доз иГКС [342].…”
Section: сывороточный эозинофильный катионный протеин (экп)unclassified
“…However, in the clinic, serum eosinophil cationic protein levels do not reflect treatment-induced functional changes in chronic asthmatics, and serum eosinophil cationic protein is unable to predict steroid responsiveness 14. One randomized trial demonstrated that patients whose asthma management was based on serum eosinophil cationic protein levels experienced no improvement in symptoms compared with those treated using traditional monitoring techniques 41. In addition, raised serum eosinophil cationic protein levels may not be a specific marker of asthma, as studies in pediatric patients have demonstrated serum eosinophil cationic protein is also raised in cystic fibrosis and viral bronchiolitis 42…”
Section: Non-exhaled Biomarkersmentioning
confidence: 99%